Miguel Arnedo-Gómez. Uniting Blacks in a Raceless Nation: Blackness, Afro-Cuban Culture and Mestizaje in the Prose and Poetry of Nicolás Guillén. Bucknell University Press, 2016. - Cecily Raynor (Studies in 20th & 21st Century Literature, 2019)
Review of Miguel Arnedo-Gómez. Uniting Blacks in a Raceless Nation: Blackness, Afro-Cuban Culture and Mestizaje in the Prose and Poetry of Nicolás Guillén. Bucknell UP, 2016. 274 pp.
Keywords: cuban poetry; race; mestizaje; afro-Brazilian identity; Latin American literature